Endophytic Fungi - An Untapped Source of Potential Antioxidants - Mishra, Rahul C.; Goel, Mayurika; Barrow, Colin J.; Deshmukh, Sunil K. (Current Bioactive Compounds, 2020)
Background: Antioxidants are the substances that interact inside and outside of a biological system against the damaging effects of highly reactive free radicals produced during metabolism. Among various natural alternative sources of bioactive metabolites, endophytic fungi have emerged as a significant reservoir of potent antioxidant compounds. These scantly explored micro-organisms are prolific producers of novel compounds and have the capability to produce metabolites that are exclusively isolated from Plantae. A wide array of compounds like nucleobases, polyketides, terpenoids, flavonoids, coumarins, xanthones, semiquinones, peptides, and phenolic acids have been identified as natural antioxidants produced by these micro-organisms. Methods: A detailed review of the literature published recently was undertaken using bibliographic database like Sci-finder and Google scholar. Questions to be reviewed and criteria for selection as a part of the study were fixed. The key features like information on the structure of isolated metabolites and antioxidant activities were summarised after a critical examination. A skeleton was established which gives insight into the type of novel chemical moieties which can be explored as a future antioxidant (s). Results: The review substantially covers the recently discovered compounds, in the period 2013 – 2018, having potent antioxidant activity, isolated from endophytic fungi colonizing diverse plant types such as terrestrial plants, mangrove plants and marine algae. Among the 96 compounds discussed here, thirtynine are from the first report of their occurrence. The present study reports 96 compounds obtained from 34 endophytic fungi out of which 15 fungi belonging to 13 genera of Ascomycetes produced 44 compounds, 14 fungi belonging to 5 genera of hyphomycetes yielded 33 compounds and 6 fungi belonging to 2 genera of Coelomycetes yielded 19 compounds. The antioxidant potency of these compounds against different free radicals is briefly described and some details such as host organisms, plant sources, place of collection and the antioxidant properties of these compounds are tabulated in this review. Conclusion: Some of these free radical scavengers have shown wide applications in the food and pharmaceutical industry as potential food preservatives, nutraceuticals, antibacterial, anticancer and antifungal agents. This review aims at highlighting some of the novel compounds isolated recently from endophytic fungi, and their applications as potential antioxidant candidates.
Keywords: Antioxidants